Students Perceptions of Mechanical Engineering Department of Balikpapan University and Balikpapan Foreign Language Academy Semester I on The Application of the RQA(Reading, Questioning, And Answering) Method in English Courses - Era Wahyu Ningsih; Fitrahnanda Ayubadiah (Prologue: Journal on Language and Literature, 2023)
This research discusses RQA (Reading, Question, and Answer), This RQA learning model is a newly developed model taking into account the fact that all students who are given reading assignments are not interested in reading the assignment. This strategy forces students to read the material given because this strategy requires them to use reading texts, and then answer the questions, students formulate questions so that they force students to think critically and think maximally about the things they have read, The implementation of RQA can motivate undergraduate students to read the assigned material and have an impact on improving the understanding of learning material. These findings provide valuable insights into how students perceive and experience the RQA method in their English learning activities. However, to enhance the comprehensiveness of your research report, you might consider providing direct quotes from participants to illustrate their views and experiences. Additionally, you could discuss the implications of these findings for educators and curriculum developers, such as the need for clearer guidance on RQA method implementation and the advantages of using text in a concise format.